Association between primary headaches and temporomandibular disorders A systematic review and meta-analysis - Reus, Jessica Conti; Polmann, Helena; Mendes Souza, Beatriz Dulcineia; Flores-Mir, Carlos; Godoi Goncalves, Daniela Aparecida [UNESP]; Queiroz, Luiz Paulo de; Okeson, Jeffrey; Canto, Graziela De Luca (Amer Dental Assoc, 2022)
Background. The primary objective of this systematic review was to answer the following question systematically: Is there any association between primary headaches (PHs) and temporomandibular disorders (TMDs) in adults? Types of Studies Reviewed. The protocol was registered with the International Prospective Register of Systematic Reviews. The authors performed the search in 6 main databases and 3 gray literature sources. The included articles had to have adult samples. PHs must have been diagnosed using the International Classification of Headache Disorders, and TMDs must have been diagnosed using Research Diagnostic Criteria for Temporomandibular Disorders, Diagnostic Criteria for Temporomandibular Disorders, or International Classification of Orofacial Pain. Risk of bias was evaluated using the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument tools. The meta-analysis was performed using Review Manager software, Version 5.4. Certainty of evidence was screened according to Grading of Recommendations Assessment, Development and Evaluation. Results. Nine of 2,574 articles reviewed met the inclusion criteria for qualitative analysis and, of these, 7 met the inclusion criteria for quantitative analysis. Odds ratios (ORs) for painful TMD and tension-type headache (OR, 1.94 [95% CI, 0.56 to 6.76] to OR, 7.61 [95% CI, 1.84 to 31.48]), migraines (OR, 4.14 [95% CI, 1.38 to 12.43] to OR, 5.44 [95% CI, 3.61 to 8.21]), and chronic headaches (OR, 40.40 [95% CI, 8.67 to 188.15] to OR, 95.93 [95% CI, 12.53 to 734.27]) were calculated. Articular TMDs without pain were evaluated in 2 articles, and both did not show positive association with tension-type headache nor migraine. Three studies were classified as moderate risk of bias and 6 as low risk of bias. The certainty of evidence varied between very low and low. Conclusions and Practical Implications. Recognizing the positive association between painful TMD and PHs can help dentists and physicians treat the pain and avoid it, or recommend the patient to a specialist.
Keywords: Headache disorders; primary; migraine disorders; tension-type headache; temporomandibular disorder; systematic review